Point Prevalence Survey of Antimicrobial Prescribing in a Nigerian Hospital: Findings and Implications on Antimicrobial Resistance (2020)
BACKGROUND: Antimicrobial resistance is a global health challenge. There is inadequate information on antimicrobial prescribing practices in many sub-Saharan African countries including Nigeria. A standardized method for surveillance of antimicrobial use in hospitals was employed to assess the antimicrobial prescribing practices in UCH, Ibadan, Nigeria. METHODS: A point prevalence survey (PPS) was conducted in December 15, 2017 at the UCH Ibadan. The survey included all in-patients receiving an antimicrobial on the day of PPS. Data collected included details on the antimicrobial agents, reasons and indications for treatment as well as a set of quality indicators. A web-based application was used for data-entry, validation and reporting as designed by the University of Antwerp (www.global-pps.be). RESULTS: This survey included 451 patients from 38 different wards of which 59.6% received at least one antimicrobial. The neonatal medical wards contributed the highest number of patients who received antibiotics. A total of 172 therapeutic antibiotic prescriptions were issued, mainly for Community- Acquired Infections (n=119; 69.2%). Most prescriptions for Healthcare Associated Infections (n=53) were intervention related (47.2%). Frequently used antibiotics include third generation cephalosporins (23.9%; mainly ceftriaxone); followed by combination of penicillin's (17.4%; mainly amoxicillin with enzyme inhibitor) and fluoroquinolones (16.6%). Majority, 312(69.9%) of the patients had parenteral antibiotics and only 95 (21.3%) of all antibiotic prescriptions had a documented stop or review date. Although the reason for antibiotic prescription was indicated for 413 (92.4%) prescriptions, targeted therapy was the basis for only 17 (3.8%) of these prescriptions. For surgical prophylaxis, 98.7% of all prescriptions were given for more than one day. Compliance to guidelines was non-existent. CONCLUSION: Our findings showed high broad spectrum prescribing, high number of intervention related health care infections, high use of prolonged surgical prophylaxis, inexistence of local guidelines; and low utilization of laboratory facilities. Hospital related intervention should include development of antibiotic guideline and increased enlightenment on rational prescribing practices.